2010
DOI: 10.3168/jds.2009-2822
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the bacterial biodiversity in koumiss by denaturing gradient gel electrophoresis and species-specific polymerase chain reaction

Abstract: Bacterial biodiversity in traditional koumiss fermented milk was studied by denaturing gradient gel electrophoresis (DGGE). Target DNA bands were identified according to the reference species ladder, constructed in this study. Comigrating bands present in the DGGE profiles were resolved by species-specific PCR. The results revealed a novel bacterial profile and extensive bacterial biodiversity in koumiss. The dominant lactic acid bacteria included Lactobacillus acidophilus, Lactobacillus helveticus, Lactobacil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 30 publications
3
21
1
Order By: Relevance
“…Of the 16 strains, 7 strains (K03, K05, K06, K07, K08, K09 and K10) were identified as Lactobacillus helveticus (44%); 5 strains (K12, K14, K15, K16 and K17) were identified as Lactobacillus acidophilus (31%); 2 strains (K21 and K22) were identified as L. plantarum (12.5%); and 2 strains (K23 and K25) were identified as Lactobacillus casei (12.5%). L. helveticus was isolated from each sample; L. acidophilus was isolated from each sample except for samples K and N; L. plantarum was only isolated from samples K and J; and L. casei was only isolated from samples K and N. The experimental results presented here are partially in accordance with the observations of Hao et al (2010), who found through the use of polymerase chain reaction and denaturing gradient gel electrophoresis (PCR-DGGE) that the dominant lactobacilli in the Xinjiang koumiss include L. acidophilus, L. helveticus, Lactobacillus fermentum, and Lactobacillus kefiranofaciens. In this study, both L. plantarum and L. casei were isolated from the koumiss samples instead of L. fermentum and L. kefiranofaciens.…”
Section: Isolation Of the Lactobacillisupporting
confidence: 92%
“…Of the 16 strains, 7 strains (K03, K05, K06, K07, K08, K09 and K10) were identified as Lactobacillus helveticus (44%); 5 strains (K12, K14, K15, K16 and K17) were identified as Lactobacillus acidophilus (31%); 2 strains (K21 and K22) were identified as L. plantarum (12.5%); and 2 strains (K23 and K25) were identified as Lactobacillus casei (12.5%). L. helveticus was isolated from each sample; L. acidophilus was isolated from each sample except for samples K and N; L. plantarum was only isolated from samples K and J; and L. casei was only isolated from samples K and N. The experimental results presented here are partially in accordance with the observations of Hao et al (2010), who found through the use of polymerase chain reaction and denaturing gradient gel electrophoresis (PCR-DGGE) that the dominant lactobacilli in the Xinjiang koumiss include L. acidophilus, L. helveticus, Lactobacillus fermentum, and Lactobacillus kefiranofaciens. In this study, both L. plantarum and L. casei were isolated from the koumiss samples instead of L. fermentum and L. kefiranofaciens.…”
Section: Isolation Of the Lactobacillisupporting
confidence: 92%
“…As has been previously reported, koumiss also has some beneficial influence on enhancing immunity, treating tuberculosis and cardiovascular disease (Wang et al, 2008). Previous studies on the bacterial biodiversity in koumiss carried out in our laboratory using denaturing gradient gel electrophoresis (DGGE) revealed that lactic acid bacteria (LAB) were predominant (Hao et al, 2010). In general, the health-care functions of koumiss are considered to directly relate to the antimicrobial compounds produced by indigenous LAB (Montanar, Zambonelli, Grazia, Kamesheva, & Shigaeva, 1996).…”
Section: Introductionmentioning
confidence: 92%
“…Based on this fact, various independent cultivation methods have been developed during the last two decades (Theron and Cloete, 2000;Jany and Barbier, 2008;Pogacic et al, 2010). During the last decade, numerous studies have evaluated the bacterial communities of fermented milk products using PCR-denaturing gradient gel electrophoresis (PCR-DGGE) but less information is available on fermented milk products from Inner Mongolia and Mongolia (Hao et al, 2010;Miyamoto et al, 2010;Liu et al, 2012). Furthermore, minor knowledge is accessible on the construction of 16S rRNA clone libraries to evaluate the microbial communities of untreated and treated milk products (Callon et al, 2007;Rasolofo et al, 2010;Raats et al, 2011;Osvik et al, 2013).…”
Section: Introductionmentioning
confidence: 97%